KINERJA INSPEKTORAT PROVINSI JAWA TENGAH - Amini, Amini; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
This Research will analylize the performance of Central Java Provincial Inspectorate and and dimensions that support or hamper the performance of the agency. The theory used in this research is the theory of public administration and five dimensions of performance that the quality, quantity, timeliness, cost effectiveness, and accountability with descriptive qualitative research design. Data collection techniques used through interviews, observation and documentation with information from employees Inspectorate of Central Java province. The results of this research indicate that the performance of Central Java Provincial Inspectorate of encouraging the implementation of good local government in Central Java is still less than optimal, especially in terms of cost effectiveness, were found problems such as limited human resources, budget and infrastructure that support the performance. Nonetheless, the performance of Central Java Provincial Inspectorate has been supported by a program whose activities have been scheduled, the training and technical guidance to improve the quality of employees, compliance program with the vision of the service, giving recommendations on the examination results on education, discipline Inspectorate of Central Java province in reporting its performance, their efforts to optimize existing resources, to the Central Java Provincial Inspectorate website as a form of performance transparency to the public. Regarding the issue, there are some suggestions that can be done such as improving the quality of existing resources, the addition of the proposed budget and infrastructure to be more adequate.